Exploration of the Effect of Multiple Charges in the Teaching of Electrostatics - SILVA, JIZREEL PEREIRA (PILLAR OF PHYSICS EDUCATION, 2023)
The paper presents the theme addressed in the classroom for students of the 3rd year of high school, in a public school in São Cristóvão, Rio de Janeiro, with the objective of extracting information through the exploration of the effects of multiple loads in the teaching of electrostatics. Two principles of electrostatics were addressed, such as load conservation and quantization of electrical load, being fundamental points for the experimental realization. The theoretical foundation was based on John Dewey is arguments, emphasizing the need for the use of experiments in science classes, conditioning the student to be the protagonist of the educational process, as well as that of Paulo Freire, so that students participate in the activities with critical and reflective posture, raising hypotheses and arguments necessary for the construction of their own knowledge. We initially discuss theoretically the fundamental aspects of the electrical charge, with the initial discoveries of the Greeks, traveling through scientists at various times in history, working on the development and improvement of electricity. We applied an experimental activity to explore and complement the exposed treatment on the interactions of electrical charges, with the division of two groups, so that students discuss with each other and work to support the assumption, according to the determinations of the questions of the virtual experiment. We discuss the results, dialoguing with the students the possibilities and facts determined by physics.